The Contribution Of Artificial Intelligence To The Development Of The Emergency Services System In The Kingdom Of Saudi Arabia: A Descriptive And Analytical Study (The Review of Diabetic Studies, 2025)
This study aims to analyze the contribution of artificial intelligence technologies in developing the emergency services system in the Kingdom of Saudi Arabia, by relying on a descriptive analytical approach for a sample of (200) individuals, whose data were collected using a questionnaire containing (12) items distributed on a three-point Likert scale. The results showed that sample members strongly favored the role of artificial intelligence in improving response speed, increasing diagnostic accuracy, and enhancing the efficiency of training and field support for emergency teams. The results also showed that technical challenges (such as difficult infrastructure) and human challenges (such as resistance to change) still represent obstacles to the optimal use of these technologies. The study recommends enhancing investment in digital infrastructure, intensifying specialized training programs for Red Crescent teams, and creating a legislative and regulatory environment that supports the integration of artificial intelligence into the emergency and ambulance sector, in line with the goals of Saudi Vision 2030.